The financialization of food? - Valentina G. Bruno; Bahattin Buyuksahin; Michel A. Robe (Bank of Canada, 2013)
Commodity-equity and cross-commodity return co-movements rose dramatically after the 2008 financial crisis. This development took place following what has been dubbed the 'financialization' of commodity markets. We first document changes since 2000 in the intensity of speculative activity in grain and livestock futures. We then use a structural VAR model to establish the role of speculative activity in explaining the strength of co-movements between grain, livestock and equity returns. We find that speculative intensity does not in itself affect the extent to which grain markets move in sync with the stock market. Rather, pre-crisis, financial speculators' futures positions facilitated the transmission of macroeconomic shocks into grain markets. Strikingly, in the post-crisis period, this transmission channel weakened to the point of statistical insignificance. The role of speculative activity is less evident in livestock markets, where only macroeconomic conditions have a statistically significant impact on return co-movements with equities.
Keywords: Q11; Q13; G12; G13; 330; International topics; Recent economic and financial developments